2011
DOI: 10.7740/kjcs.2011.56.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Activities of Fermented Rice Bran from Novel Black Colored Rice Cultivar SuperC3GHi

Abstract: Rice bran is by-product from the dehulling process of rice, an important staple food in Korea. Various studies have been reported immune-enhancing effects of rice bran cultured with Lentinus edodes. In particular black rice bran that contains anthocyanin has the beneficial effects on immune system. SuperC3GHi, a recently released black colored rice cultivar, has higher contents of cyanidine-3-glucoside (C3G), a strong antioxidant than those of currently cultivated black rice cultivars. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Analysis of histamine secretion also showed a similar trend, with a statistically significant 18% reduction (p < 0.05) recorded in mast cells treated with 100 µg/mL fermented SuperC3GHi bran and 43% with 250 µg/mL. Further experiments were carried out by Kim et al [85] to assess the anti-inflammatory effect of fermented SuperC3GHi bran in an ear-oedema mice mode. Arachidonic acid (3%) was applied to the ears of ICR mice to induce inflammation via increased production of prostaglandins.…”
Section: Kim Et Al (2011) [85]mentioning
confidence: 58%
See 4 more Smart Citations
“…Analysis of histamine secretion also showed a similar trend, with a statistically significant 18% reduction (p < 0.05) recorded in mast cells treated with 100 µg/mL fermented SuperC3GHi bran and 43% with 250 µg/mL. Further experiments were carried out by Kim et al [85] to assess the anti-inflammatory effect of fermented SuperC3GHi bran in an ear-oedema mice mode. Arachidonic acid (3%) was applied to the ears of ICR mice to induce inflammation via increased production of prostaglandins.…”
Section: Kim Et Al (2011) [85]mentioning
confidence: 58%
“…Similarly, Kim et al [85] confirmed that treatment with fermented SuperC3GHi bran (100 and 250 µg/mL) significantly reduced (p < 0.05) the release of β-hexosaminidase from RBL-2H3 mast cell line stimulated with the allergen sensitiser Compound 48/80. The β-hexosaminidase activity of mast cells was decreased by 25% (100 µg/mL) and 40% (250 µg/mL) compared to the control with no treatment.…”
Section: Kim Et Al (2011) [85]mentioning
confidence: 70%
See 3 more Smart Citations